Representation of Religious Values in the Acehnese Manuscript of Hikayat Tambeh Tujoh - Nina Eka Putri; Roslan Bin AB. Rahman (Darul Ilmi Bina Insan Foundation, 2026)
This research focuses on the urgency of preserving Aceh's old literary culture. This research aims to examine the content of the Hikayat “Tambeh Tujoh” manuscript and the religious values contained in it Using a qualitative approach with literature review methods, the study analyzes the manuscript, which contains seven chapters of advice and warnings. The manuscript consists of ten sections, including an introduction and specific chapters discussing topics such as marriage advice, physiognomy, medical knowledge, essential traits of believers, stinginess, and the inevitability of death and resurrection. The religious values within the text are categorized into: (1) Sharia values, emphasizing the six pillars of faith; (2) Creed values, reflected in discussions of Usul Fiqh and Islamic jurisprudence; and (3) Moral values, spanning from the opening section to the seventh chapter. These religious teachings highlight the spiritual and ethical foundations in the hikayat and offer insight into Aceh’s rich literary and cultural history